KREATIVITAS DAN INOVASI USAHA MELENIAL DUKUNG PEREKONOMIAN NEGARA DITENGAH PANDEMI COVID –19 - Sudiyarti Sudiyarti (Prodi Ilmu Administrasi Negara, 2020)
The theme of melenial business management has a definition that is: managing or regulating human needs individually in particular and for society in general. Efforts to be inspired from contact, through the world of digital business and the Internet, in the midst of the covid-19 pandemic outbreak, with efforts and innovations and technological developments so that it will greatly support the country's economy. In the business world, the melenial generation is believed to bring change and become an economic power in particular in Indonesia and in developing countries in general. In addition to being active as Internet users, the current generation can also strengthen opportunities in times of crisis gelobal such as at this time, to earn income during the Covid-19 Pandemic as it is today.